STRATEGIES OF COPING WITH DIFFICULTIES DURING RESEARCH PERFORMED BY YOUNG SCIENTISTS - Tatiana G. Bokhan; Marina V. Shabalovskaya; Irina Yu. Malkova; Oksana N. Galazhinskaya; Lyubov V. Radishevskaya (National Research Mordova State University, 2017)
Introduction: young scientists engaged in creative activities face difficulties during scientific research, implementation and commercialisation of the results. The impossibility of coping with obstacles leads to the impairment of motivational and creative activity. The problem of studying the main semantic contents of difficult situations and strategies to cope with them becomes relevant as it is conducive to the process of personal development of young scientists. Materials and Methods: the authors used a questionnaire with open-ended questions for revealing the main difficulties and coping strategies in the process of research activity; COPE questionnaire adapted by E. Rasskazova, T. Gordeyeva, E. Osin; Style of Self-Regulation of Behaviour technique by V. I. Morosanova. Statistical data processing was carried out with descriptive statistics methods, analysis of frequencies, factor analysis (Varimax rotation with Kaiser normalisation), cluster analysis (furthest neighbour method and Ward's method). Results: eight main semantic categories related to difficulties experienced in the process of performing the research work have been detected. The main ways of coping with arising difficulties have been identified. Types of respondents different in terms of coping strategies and regulatory-behavioural characteristics have been distinguished. Discussion and Conclusions: difficulties of self-organisation in time for realisation of new meanings, difficulties in structuring the research work and search for information act as psychological barriers provoking mental stress. The most efficient coping strategies in respondents are strategies Active coping and search for positive meaning and personal development. The inefficient coping strategy with difficulties complicating the process of self-development is Avoiding problems strategies.